Kualitas Daging Ikan Kurisi (Nemipterus japonicus) Hasil Tangkapan Nelayan di Pelabuhan Perikanan Branta, Pamekasan: Quality of Kurisi Meat (Nemipterus japonicus), Results of Fisherman Catching in Branta Fishing Port, Pamekasan - Abdus Salam Junaedi; Fortunata Riana; Harfatia Chandra Puspita Sari; Witria Witria; Muhammad Zainuri (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2020)
Quality control over the catch of fishermen in the Branta Fishery Port, Pamekasan is still not well-implemented. This study was aimed to evaluate the quality of kurisi fish meat based on the value of the Total Plate Count (TPC), diversity and total heterotrophic bacteria and pathogens on TSA, EMB, SSA, and TCBS media. The heterotrophic bacterial TPC (TSA) value was 8.59 Log CFU/g with 7 species diversity and the highest total of species abundance was between 2-336 colonies (BH3). The pathogenic bacterial TPC (EMB) value was 3.72 Log CFU/g with 6 species diversity and the highest total of species abundance was between 784-1009 colonies (BPE4). The BPE1 bacterial isolate which was metallic green was suspected to be Escherichia coli. The pathogenic bacterial TPC (SSA) value was 4.12 Log CFU/g with 5 species diversity and the highest total of species abundance was between 35-450 colonies (BPS1), and the BPS1 bacterial isolate which was black was suspected to be Salmonella sp. The pathogenic bacterial TPC (TCBS) value was 5.41 Log CFU/g with 2 species diversity and the highest total of species abundance was between 0-44 colonies (BPT1). The green and yellow BPT1 and BPT2 bacterial isolate were suspected to be Vibrio parahaemolyticus and Vibrio vulnificus.